Potensi Antioksidan dan Inhibitor α-Glukosidase dari Isolat Bakteri Endofit Daun Pandan Wangi (Pandanus amaryllifolius Roxb.) - Nabila Hasibuan; Edy Fachrial; Novitaria Br Sembiring (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Background: Diabetes mellitus is a chronic metabolic disease with an increasing prevalence and risk of serious complications. Inhibition of the α-glucosidase enzyme is a strategy to control blood glucose levels. Endophytic bacteria from fragrant pandan leaves (Pandanus amaryllifolius Roxb.) have the potential to produce bioactive compounds, such as flavonoids, which possess antioxidant and α-glucosidase inhibitory activities. Objective: This study aimed to isolate endophytic bacteria from fragrant pandan leaves and evaluate the antioxidant and α-glucosidase inhibitory activities of the culture supernatant of these endophytic bacterial isolates as natural antidiabetic candidates. Methods: The research included characterization of endophytic bacterial isolates, antioxidant assay using the DPPH method, and α-glucosidase inhibition assay using pNPG substrate. The supernatant of the endophytic bacterial culture was tested to determine the percentage of inhibition against DPPH radicals and α-glucosidase enzyme. Results: The results showed that endophytic bacterial isolate code P8 exhibited 75% antioxidant activity and 97% α-glucosidase inhibitory activity. The α-glucosidase inhibitory activity of isolate P8 was higher than that of the positive control acarbose (81%). Conclusion: Endophytic bacterial isolate P8 from fragrant pandan leaves has potential as a source of natural antidiabetic bioactive compounds with potent antioxidant and α-glucosidase inhibitory activities, and potentially minimal side effects.